Making concentrated solar power competitive with coal: The costs of a European feed-in tariff - Williges, Keith; Lilliestam, Johan; Patt, Anthony (Energy Policy, 2010)
The European Union has yet to determine how exactly to reach its greenhouse gas emissions targets for the future. One potential answer involves large-scale development of concentrated solar power (CSP) in the North African region, transmitting the power to Europe. CSP is a relatively young and little utilized technology and is expensive when compared to other methods of generation. Feasibility studies have shown it is possible to generate enough power from CSP plants in Africa to spearhead the EUs climate goals. However, the costs of such a project are less well known. Currently, CSP must compete with low cost coal-fired electricity plants, severely hindering development. We examine the possible investment costs required for North African CSP levelized electricity cost to equal those of coal-fired plants and the potential subsidy costs needed to encourage growth until the technologies reach price parity. We also examine the sensitivity of investment and subsidies to changes in key factors. We find that estimates of subsidy amounts are reasonable for the EU and that sensitivity to such factors as perceived risk and learning rates would enable policy-makers to positively influence the cost of subsidies and time required for CSP to be competitive with coal. © 2010 Elsevier Ltd.
CRIS-Team Scopus Importer:2023-06-14
Keywords: Concentrated solar power; Induced technological learning; Supergrid